Effects of 1-MHz Ultrasound on Epaxial Muscle Temperature in Horses - Adair, Henry S.; Levine, David (Frontiers in Veterinary Science, 2019)
Objective: The purpose of this study was to examine the tissue temperature changes that occur at various depths during 1.0-MHz ultrasound (US) treatments of the epaxial muscles in horses. Animals: Ten healthy adult mares with no lameness or orthopedic disease weighing between 465 – 576 kg were studied. Procedures: Two 1.0-MHz US treatments, one at an intensity of 1.0 W/cm2 and one at 2.0 W/cm2, were administered to the epaxial region. Needle thermistors were inserted in the epaxial muscles below the skin surface at depths of 1.0, 3.0, and 5.0 cm, directly under the US treatment area. Depths were verified with diagnostic ultrasound. Both intensities of US treatment were performed on each horse over a 20 cm2 area for 10 minutes using a sound head with an effective radiating area of 10 cm2. Treatments were administered in random order. Tissue temperature was measured before, during, and for an additional 10 minutes after the end of US treatment. Data was recorded at 30 second intervals for each treatment condition and used for statistical analysis. Results: At the completion of the 10 minute US treatment, the temperature rise at an intensity of 1.0 W/cm2 was 1.70°C at the 1.0 cm depth, 1.03°C at 3.0 cm depth, and 1.23°C at 5.0 cm depth. At an intensity of 2.0 W/cm2, temperatures rose 2.61°C at the 1.0 cm depth, 1.15°C at 3.0 cm depth, and 1.93°C at 5.0 cm depth. Conclusion and Clinical Importance: This study demonstrates that significant heating occurs in the epaxial muscles of horses during 1.0-MHz US with the greatest heating occurring at a depth of 1.0 cm.